Nickel and cobalt Co-substituted spinel ZnMn2O4@N-rGO for increased capacity and stability as a cathode material for rechargeable aqueous zinc-ion battery. (20th January 2020) - Tao, Yayuan; Li, Zhi; Tang, Linbin; Pu, Xiaoming; Cao, Tong; Cheng, Danhong; Xu, Qunjie; Liu, Haimei; Wang, YongGang; Xia, Yongyao
Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) are possible future replacements for large-scale energy storage devices because of their safety, low cost, and abundance of materials. Finding a competitive cathode material suitable for zinc-ion insertion/de-insertion, needed to achieve high reversible capacity and long cycle stability, is one of the most important and arduous challenges. For the first time, nickel and cobalt co-substituted spinel ZnMn2 O4 nanoparticles, homogeneously loaded onto N-doped reduced graphene oxide (ZnNix Coy Mn2-x-y O4 @N-rGO), were synthesised through a one-step hydrothermal method and applied as a cathode material to accommodate the intercalation of zinc ions. The as-prepared ZnNix Coy Mn2-x-y O4 @N-rGO displayed excellent electrochemical performance, with a reversible capacity of 95.4 mA h g −1, achieved at 1000 mA g −1 after 900 cycles, and a capacity retention ratio of 79%. When the current density increased from 10 mA g −1 to 1500 mA g −1, high capacity (200.5 mA h g −1 to 93.5 mA h g −1 ) was achieved, which was much higher than that of ZMO@N-rGO without nickel and cobalt co-substituting (184 mA h g −1 to 59.2 mA h g −1 ), demonstrating excellent rate performance. These excellent electrochemical properties are attributed to the co-substituting of nickel and cobalt elements, which is an effective approach to promote Zn 2+ de-intercalation and to stabilize the spinel structure in order to suppress the Jahn-Teller distortion of Mn 3+ . Therefore, nickel and cobalt co-substituting of spinel ZnMn2 O4 @N-rGO with a stable structure opens up new possibilities for large-scale application of rechargeable, aqueous ZIBs. Graphical abstract: Image 1 Highlights: Nickel and cobalt co-substituted spinel ZnMn2 O4 nanoparticles were synthesised The ultrafine ZnNi0.39 Co0.59 Mn0.98 O4 loaded onto N-doped reduced graphene oxide. The ZnNi0.39 Co0.59 Mn0.98 O4 @N-rGO exhibited excellent performance as a cathode for SIBs. Nickel and cobalt co-substituting stabilized the spinel structure. The N-doped graphene network ensured highly electronic conductivity.